The Focusing Effect in Negotiations - Andrea Canidio; Heiko Karle (Center for Economic Studies and ifo Institute (CESifo), 2021)
Two players with preferences distorted by the focusing effect (Koszegi and Szeidl, 2013) negotiate an agreement over several issues and one transfer. We show that, as long as their preferences are differentially distorted, an issue will be inefficiently left out of the agreement or inefficiently included in the agreement whenever the importance of the other issues on the table is sufficiently large. Anticipating this possibility, the negotiating parties may negotiate in stages, by first signing an incomplete agreement and later finalizing the outcome of the negotiation. Negotiating in stages increases the efficiency of the negotiation, despite the fact that the players' preferences are distorted by the focusing effect also when negotiating the incomplete agreement.
Keywords: C78; D03; D86; F51; 330; salience; focusing effect; bargaining; negotiations; incomplete agreements